Propuesta de un modelo de responsabilidad social empresarial en los Centros comerciales del sector sur de Quito - Espinosa Fajardo, María Estefanía (2014)
This research mainly aims at analyzing corporate social responsibility and propose a strategic model of social responsibility for the commercial centers of southern sector of Quito, focused on Commercial City "El Recreo". A qualitative approach was used, with descriptive study in this research because the current situation of the Trade City "El Recreo" is I investigate; secondary sources such as the Internet, books, magazines and bibliographies corresponding records was used.